Cold Plasma Modeling for Air Pollution Control: NOx Removal in Dielectric Barrier Discharge Reactors - Nesrine Labdouni; Djilali Benyoucef; Hocine Tebani (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
The paper presents a comprehensive numerical investigation of dielectric barrier discharges (DBDs) operating in atmospheric pressure air (N₂–O₂–Ar) containing NO concentrations between 2.5% and 10% is presented for plasma assisted NOₓ mitigation. A one-dimensional fluid model is developed to describe the discharge dynamics and plasma chemical interactions under applied voltages of 8–12 kV and excitation frequencies of 2–4 kHz. The influence of voltage amplitude and frequency on electrical characteristics and NOₓ removal efficiency is systematically analyzed. A representative operating condition (10% NO, 10 kV, 3 kHz) is examined in detail to elucidate the temporal evolution of voltage and current and the spatial distributions of electrons, ions, excited species, and neutral particles involved in NO dissociation pathways. The results provide improved insight into the reaction kinetics governing NO degradation in air plasma and offer practical guidance for optimizing DBD-based environmental remediation systems. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).